Diffraction of Electromagnetic Waves on a Multi-Layer Structure of Metal Screens with Rectangular Holes - Gribovsky, A. V.; Litvinenko, L. M.; Prosvirnin, S. L. (Видавничий дім «Академперіодика», 2013)
Diffraction of Electromagnetic Waves on a Multi-Layer Structure of Metal Screens with Rectangular Holes